Presentation slides: What do we know about the future of rice and fish in relation to food systems transformation? - Valera, Harold Glenn; Chan, Chin Yee (2023)
This was a PowerPoint presentation presented during the International Rice Congress, Manila, Philippines, October 16-19, 2023 - https://www.irri.org/IRC2023-teaser.html